Efficacy and Safety of Anticoagulants for COVID-19 Patients in the Intensive Care Unit: A Systematic Review and Meta-Analysis - yulistiani; Vina Neldi; Budi Suprapti; Alfian Nur Rosyid (Frontiers Media S.A., 2022)
Purpose: This study aims to analyze the efficacy and safety of anticoagulants for COVID-19 patients in the intensive care unit. Methods: A comprehensive search was conducted using databases such as MEDLINE, PubMed, EuropePMC, Science Direct, Google Scholar, Clinicaltrial.gov, The Cochrane Central Register of Controlled Trial (CENTRAL, Cochrane Library) and several other published articles from the systematic review up to March 31, 2021. The Newcastle-Ottawa Scale (NOS) was used for the studies' qualitative assessment. The primary outcome examined was mortality rate, while the secondary included the length of stay (LOS) in thei care unit; hospital length of stay (HOS), coagulation markers including D-dimer, Platelet count, aPTT, PT and fibrinogen; markers of inflammation specifically C-reactive protein; and other adverse events ranging from hemorrhage to thrombosis. Additionally, the quantitative synthesis was conducted using fixed and random effects model in "The Revman 5.4", while heterogeneity was tested using the I-squared (I2) measure. Results: A total of 1,062 articles were found during the initial search step and eventually 12 were chosen to be analyzed quantitatively in a meta-analysis. Comparison of the results related to anticoagulant group with no anticoagulant or standard care treatment showed that anticoagulant group significantly reduced mortality rate with RR= 0.53; 95 % CI, 0.30-0.95; P= 0.03, with I2 = 88% and venous thromboembolism (VTE) RR = 0.53; 95% CI, 0.37-0.76; P = .0007 with I2 = 35%. Conclusions: Based on the results, anticoagulants can mitigate mortality rate and VTE in COVID-19 patients.